Homogeneous Elongation of N‐Doped CNTs over Nano‐Fibrillated Hollow‐Carbon‐Nanofiber: Mass and Charge Balance in Asymmetric Supercapacitors Is No Longer Problematic. Issue 20 (14th May 2022) - Kim, Taewoo; Subedi, Subhangi; Dahal, Bipeen; Chhetri, Kisan; Mukhiya, Tanka; Muthurasu, Alagan; Gautam, Jagadis; Lohani, Prakash Chandra; Acharya, Debendra; Pathak, Ishwor; Chae, Su‐Hyeong; Ko, Tae Hoon; et al.
Abstract: The hurdle of fabricating asymmetric supercapacitor (ASC) devices using a faradic cathode and a double layer anode is challenging due to the required large amount of active mass of anodic material compared to that of the cathodic material during mass balancing due to the large difference in capacitance values of the two electrodes. Here, the problem is addressed by engineering a negative electrode that furnishes an ultrahigh capacitance. An in situ developed metal–organic framework (MOF)‐based thermal treatment is adopted to grow highly porous N‐doped carbon nanotubes (CNTs) containing submerged Co nanoparticles over nano‐fibrillated electrospun hollow carbon nanofibers (HCNFs). The optimized CNT@HCNF‐1.5 furnishes an ultrahigh capacitance approaching 712 F g –1 with excellent rate capability. The capacitance reported from this work is the highest for any carbonaceous material reported to date. The CNT@HCNF‐1.5 is further used to fabricate symmetric supercapacitors (SSCs), as well as ASC devices. Remarkably, both the SSC and ASC devices furnish incredible performances in all aspects of SCs, such as a high energy density, long cycle life, and high rate capability, displaying decent practical applicability. The energy density of the SSC device reaches as high as 20.13 W h kg –1, whereas that of ASC approaches 87.5 W h kg –1 . Abstract : An in situ developed metal–organic framework‐based thermal treatment technique is adopted to prepare porous N‐doped carbon nanotubes containing firmly submerged Co‐nanoparticles over nano‐fibrillated electrospun hollow carbon nanofibers. When the optimized CNT@HCNF‐1.5 is applied as a negative electrode, the problem related to mass balancing during fabrication of asymmetric supercapacitor can be addressed satisfactorily that will open new possibilities for the future works.